2017
DOI: 10.1021/acs.energyfuels.7b00504
|View full text |Cite
|
Sign up to set email alerts
|

Wax Deposition Modeling with Considerations of Non-Newtonian Characteristics: Application on Field-Scale Pipeline

Abstract: Wax removal by pigging is costly in sub-sea oil production. Cost-effective scheduling of pigging can be achieved based on the deposition rate predicted by wax deposition models. Conventional wax deposition models predict wax deposition rates on the basis of Newtonian fluid mechanics. Such an approach can become invalid for highly waxy crude oils with non-Newtonian rheology. In this investigation, different simulation techniques, including large eddy simulation, Reynolds-averaged Naiver–Stokes equations, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 34 publications
0
47
0
1
Order By: Relevance
“…Different approaches have been used by flow assurance engineers to model wax deposition profiles inside pipelines . Recent studies have also reported experimental and modelling results for the cold flow regime ( T h < WAT) .…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been used by flow assurance engineers to model wax deposition profiles inside pipelines . Recent studies have also reported experimental and modelling results for the cold flow regime ( T h < WAT) .…”
Section: Introductionmentioning
confidence: 99%
“…The wax component in crude oil will bring a series of problems to the production and transportation of crude oil (Huang Z al., 2011;Azevedo L F A al., 2003;Xiao R G al., 2018). In order to find countermeasures, accurate acquisition of wax deposition rate model has become an important part of wax deposition research Zheng S al., 2017;José P al., 2015). However, the models of wax deposition rate are all nonlinear models, which are usually complex and difficult to obtain model parameters, which greatly restricts the engineering application and development of the models.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the process and mechanism of wax deposition in the tube, scholars generally believed that molecular diffusion is the main mechanism of wax deposition. Through a large number of experimental and theoretical studies, many valuable wax deposition models have been established by scholars (Huang Q Y, et al, 2008;Zheng et al, 2017;Noville et al, 2012;Singh et al, 2011;Amine et al, 2008;Sadra et al, 2014;Brown et al, 1993;Eskin et al, 2014). In the process of establishing the wax deposition model, the determination of temperature gradient and concentration gradient is very important.…”
Section: Introductionmentioning
confidence: 99%